UJI EFEK ANALGETIKA EKSTRAK BUAH KAKTUS (Opuntia elatior Mill.) PADA MENCIT (Mus musculus) YANG DIINDUKSI ASAM ASETAT - Gissa Amellia; Ihwan Ihwan; Akhmad Khumaidi (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2015)
Pain is a mechanism of body defense. One way to allay or decreasing the pain is using medicines that have analgetic effect. The aim of this study is determine the analgetic effect of cactus fruits (Opuntia elatior Mill.) extract and the most effective dose to giving analgetic effect. This study used writhing method by the injection acetic acid 1% as induced. Group I as a negative control used natrium carboxy methylcellulose 1%, group II as a positive control used aspirin suspension which dosage was 1,3 mg/20g BB, group III as a extract of cactus fruits give to dose 50 mg/kg BB, group IV dose 100 mg/kg BB, and group V dose 150 mg/kg BB. The result shows that cactus fruits extract to giving analgetic effect judging from the reduction strength writhing reflex to protection percentage at dose 50 mg/kg BB (11,26%), 100 mg/kg BB (42,10%), 150 mg/kg BB(60,14%) and the positif control (75,34%), at the positif control shows that higher protection percentage. Effectiveness percentage analgetic extract of cactus fruits at dose of 50 mg/kg BB (14,4%), 100 mg/kg BB (55,36%), 150 mg/kg BB (79,95%) and positif control (100%). The data which is got from the calculation later is analyzed by Kruskal Wallis. The result showed that at dose of 150 mg/kg BB is p: 0,016 (p<0,05) when compared with the positive control. So that is different significantly between dose 150 mg/kg BB and the positive control. The extract showed a optimal analgetic effect characterized by a significant reduction in the number of writhes or abdominal stretches in mice with dose 150 mg/kg BB body weight used when compared to the cactus fruits extract dose 50 and 100 mg/kg BB